Biological radiation - Irina Zueva (African Journal of Biological Sciences, 2020)
For a long time, the scientific community has been discussing whether living beings have specific biological radiation that is different from the standard set of electromagnetic and acoustic waves occur in the process of vital activity of an organism as a whole and its parts. In this paper, the author presents the results of experiments confirming the presence of such specific biological radiation and its material nature.
Keywords: Biological radiation, Biofield, Biotron-Tszjan, Biowaveguide, Saturated water.